2017
DOI: 10.7774/cevr.2017.6.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Preferential production of IgM-secreting hybridomas by immunization with DNA vaccines coding for Ebola virus glycoprotein: use of protein boosting for IgG-secreting hybridoma production

Abstract: PurposeThe goal of this study was to investigate the utility of DNA vaccines encoding Ebola virus glycoprotein (GP) as a vaccine type for the production of GP-specific hybridomas and antibodies.Materials and MethodsDNA vaccines were constructed to express Ebola virus GP. Mice were injected with GP DNA vaccines and their splenocytes were used for hybridoma production. Enzyme-linked immunosorbent assays (ELISAs), limiting dilution subcloning, antibody purification methods, and Western blot assays were used to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 17 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…We previously reported that GP DNA vaccines induce Ag-specific antibody responses [ 10 ]. In this study, we investigated whether GP DNA vaccines might induce IgG responses to the native forms of GP expressed on the cell surface.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously reported that GP DNA vaccines induce Ag-specific antibody responses [ 10 ]. In this study, we investigated whether GP DNA vaccines might induce IgG responses to the native forms of GP expressed on the cell surface.…”
Section: Resultsmentioning
confidence: 99%
“…A GP DNA vaccine, pcDNA3-GP was previously tested [ 10 ]. It encodes GP of Zaire Ebola virus strain Gabon-94 (GenBank No.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations